ANALYTIC MODEL OF HYDRAULIC SEPARATION OF COAL SEAM - Slastunov S.V. (My University, 2001)
Methods of prevention of sudden outbursts have been considered. It has been shown that preliminary degassing of coal seams with the use of hydraulic separation of them is efficient method. Mathematical model of process of hydraulic separation of the seams has been developed on basis of linear Darsi law and continuity equation. Numerical method of calculating the parameters of the process has been created. Offered approach makes it possible to evaluate duration of water injection depending on required size of hydraulic separation zone. Necessity to minimize costs of operations has been taken into account.